Where are all the Services: Mapping Community-Based Services for Canadian Autistic Youth with Co-occurring Mental Health Conditions. - Andreasen, Stephanie; Kuntz, Jennifer; Ames, Megan E.; Coombs, E. C.; McMorris, Carly (Journal of Autism & Developmental Disorders, 2026)
Purpose: Autistic youth are at heightened risk of mental health issues and face several barriers to accessing appropriate supports. A lack of available services is a common barrier that many autistic youth experience, with only 43% of autistic youth from the US who needed mental health services receiving them. Little is known about the availability of these mental health services in Canada, despite the high prevalence of mental health issues in autistic youth. The current study is one of very few that has reviewed the state of community-based programs and services for the support of mental health challenges in autistic people in North America, and the first such study in Canada. Methods: Using an environmental scan methodology, we conducted a search of resource listings on various community websites with a filter for "autism". The resulting websites were then reviewed to find what services providers offer for autistic youth (≥ 25 years) and contacted to complete a survey. Results: 267 listings of mental health supports were identified in the initial search, with 94 sites that specifically mentioned serving autistic youth. 43% (n = 40) of service providers completed a survey about the services they offered, therapeutic approaches, and background training. Providers reported that neurodiversity approaches and multi-disciplinary teams were working well in their practices, yet funding access and society's views on autism were barriers they face. Conclusion: Findings add to the growing body of evidence that availability of services is a systemic barrier that many autistic youth experience when accessing mental health supports.